A comprehensive analysis of safety predictors in construction sites: A DEMATEL-Based Model - Kang, Chun Xiang; Chai, Changsaar; Lee, Chia Kuang (Penerbit Universiti Sains Malaysia, 2024)
The construction industry, vital for economic growth and human capital development, faces significant safety challenges, particularly in the Malaysian context. Despite technological advancements, addressing safety concerns necessitates a deeper understanding of behavioural interventions. This study explores the critical factors influencing safety compliance intention and safety participation in the Malaysian construction industry, utilising the Theory of Planned Behaviour (TPB) as its theoretical framework. TPB posits that actual behaviour can be predicted by intention, while the formation of intention is mainly determined by attitude, subjective norms and perceived behavioural control. Despite the posited framework considering TPB, there is no evidence to prove the correlation between safety predictors, safety compliance intention and safety participation. This study examines the influence of safety predictors on safety compliance intention and safety participation by using the decision-making trial and evaluation laboratory (DEMATEL) technique. Based on the DEMATEL technique, 25 experts were invited to provide pairwise ranking on the predictors influencing safety compliance intention and safety participation. The predictors examined in the study include “Attitude”, “Subjective norm”, “Perceived behavioural control”, “Types of leadership styles”, “Safety knowledge”, “Safety climate”, “Safety motivation”, “Risk perception” and “Communication”. Among these predictors, the study revealed significant relationships between all safety predictors, with “Attitude” emerging as the most impactful predictor. Organisations should prioritise this to enhance safety performance. Safety performance in construction projects can be improved and intervened in when the interrelationships between safety predictors, safety compliance intention and safety participation are fully understood.